Pengalaman Psikologis Ketidakberdayaan Post COVID-19 di Jember (Studi Kasus) - Azari, Abdul Aziz (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2020)
Introduction: Helplessness is a condition in which the individual feels unable to endure all painful and uncomfortable things that support himself. In people with post-Covid-19, the helplessness they experience tends to be the signs and symptoms they experience when suffering from Covid-19. This study aims to describe the helplessness of Covid-19 patients as long as they are attacked by Covid-19. Methods: This study used a qualitative research design with a case study approach. Participants in the study were 1 person with purposive sampling data collection technique. Data analysis using Colaizzi technique. Results: Based on the research conducted, there were several manifestations of helplessness presented by Covid-19 sufferers, emotional, motivational and behavioral symptoms; where it all decreases and affects a person's depression. Discussion: The experience of suffering from Covid-19 provides traumatic experiences for sufferers, one of which is helplessness during the Covid-19 treatment period, and this results in changes in the emotional, cognitive, and behavior of someone who has suffered from Covid-19. Keywords: helplessness, Covid-19, psychological, depression.